THE USE OF REFERENCE AS MARKERS OF PROPOSITIONAL RELATIONS IN JUNIOR HIGH SCHOOL STUDENTS’ ESSAYS - Wahid, Abdul; Sukri Syamsuri, Andi; Hasrianti, Andi; Syahrin, Alfi (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
The purpose of this study was to evaluate the use of reference as markers of propositional relations in essays written by junior high school students. This study employed a qualitative method in data collection and data analysis. The population and research samples were 94 eighth-grade students from SMP Negeri 1 in Balikpapan, Indonesia, ranging in age from 13 to 14. Data collection in this research was carried out using the listening method after the essay as a source of research data obtained from the research sample.The data analysis in this study consisted of three stages that were completed interactively: data reduction, data display, and conclusion drawing. This study suggest that participants utilized three distinct kinds of reference to denote propositional relations in their essays: third-person pronoun, non-person pronoun, and demonstrative pronoun. The third person pronoun was found to be widely used but did not vary significantly among participants. Meanwhile, participants’ usage of non-person pronouns resulted in numerous interpretations, and it was discovered that derived demonstrative pronouns were overused. These findings demonstrate the participants’ strengths and shortcomings in using reference to connect one proposition to another.